Peace, propaganda & the promised land U.S. media & the Israeli-Palestinian conflict - Media Education Foundation (Canada : Media Education Foundation, 2007)
This pivotal documentary exposes how the foreign policy interests of American political elites-working combination with Israeli public relations strategies- exercise a powerful influence over news reporting about the Israeli-Palestinian conflict.
disc 1. Main features (80 min.) -- Interviews (151 min.) -- News clips (64 min.) -- disc 2. Extra interviews (66 min.) -- short films (260 min.)
Title from title screen.
DVD format.
Keywords: Mass media -- Political aspects -- Israel; Press -- Influence; Arab-Israeli conflict -- 1973-1993 -- Mass media and the conflict; Arab-Israeli conflict -- 1973-1993 -- Press coverage -- Israel; Arab-Israeli conflict -- 1993- -- Mass media and the conflict; Arab-Israeli conflict -- 1993- -- Press coverage -- Israel